2011
DOI: 10.2478/s11534-011-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of silicon Dioxide — silica glass, α-quartz and stishovite

Abstract: Abstract:This paper compares the luminescence of different modifications of silicon dioxide -silica glass, α-quartz crystal and dense octahedron structured stishovite crystal. Under x-ray irradiation of pure silica glass and pure α-quartz crystal, only the luminescence of self-trapped exciton (STE) is detected, excitable only in the range of intrinsic absorption. No STE luminescence was detected in stishovite since, even though its luminescence is excitable below the optical gap, it could not be ascribed to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…10 The much smaller band gap of TiO 2 (anatase) (3.2 eV, ∼390 nm) compared to SiO 2 (8.5 eV, ∼145 nm) enables the reaction to utilize the UV wavelengths >300 nm with higher efficiency. 35,36 The results suggest that this role change of TiO 2 in perchlorate formation from acting solely as a UV screen under Mars conditions to photocatalyst under terrestrial conditions is caused by superoxide (O 2 − ). It has been shown that O 2 − formed at >−196 °C is not stable but that TiO 2 can stabilize O 2 − under Mars ambient conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 The much smaller band gap of TiO 2 (anatase) (3.2 eV, ∼390 nm) compared to SiO 2 (8.5 eV, ∼145 nm) enables the reaction to utilize the UV wavelengths >300 nm with higher efficiency. 35,36 The results suggest that this role change of TiO 2 in perchlorate formation from acting solely as a UV screen under Mars conditions to photocatalyst under terrestrial conditions is caused by superoxide (O 2 − ). It has been shown that O 2 − formed at >−196 °C is not stable but that TiO 2 can stabilize O 2 − under Mars ambient conditions.…”
mentioning
confidence: 99%
“…34 Because TiO 2 (anatase) has a smaller band gap (3.2 eV, ∼390 nm) than SiO 2 (8.5 eV, ∼145 nm), its ability to oxidize Cl − should be even greater than that of SiO 2 and it should still function as a photocatalyst in UVB (280−315 nm) and UVA (315−400 nm) regions where SiO 2 cannot. 35,36 Because the environments on Mars and Earth are very different, it is possible that TiO 2 could also behave very differently in each case. In this study, we determined the effects of water on perchlorate production under both dry and wet martian environments.…”
mentioning
confidence: 99%
“…Ez a tendencia esetleg azzal függhet össze, hogy a kvarcban az ionizáló sugárzás hatására kristályrácshibák pl. többféle lyuk-centrum, illetve oxigénhiány centrum alakulhat ki (TRUKHIN et al 2011), amelyek nem fénykibocsátó rekombinációs centrumokat képeznek.…”
Section: Diszkusszióunclassified
“…10 It is also known that different modifications of the silica particles exhibit luminescence maximums in different wavelength regions. 11 The luminescence properties of silica nanoparticles in the polymer matrix was also investigated by some authors. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…10 It is also known that different modifications of the silica particles exhibit luminescence maximums in different wavelength regions. 11 The luminescence properties of silica nanoparticles in the polymer matrix was also investigated by some authors. 12,13 However, there are a lot of rooms to study the structure and optical properties of polymer/silica nanocomposites, since the properties of these nanocomposites depend on the production techniques, the type of polymer, the crystallinity degree, the modification type, the size of silica.…”
Section: Introductionmentioning
confidence: 99%